Effect of drought stress on physiological traits and antioxidant activities in some olive cultivars - Gholmohammadi, Majid; Sofalian, Omid; Taheri, Mahdi; Ghanbari, Alireza; Rasoli, Valiollah (Cellular and Molecular Biology, 2019)
Drought is important abiotic stress that negatively influences the growth and development of plants. Strong efforts are currently ongoing worldwide to improve olive production under adverse environmental conditions by extending genetic diversity to improve key agro-physiological and biochemical features through various breeding programs. This research was performed to evaluate the effect of drought stress on the changes of some physiological and biochemical traits in 20 commercial and promising olive genotypes under field conditions during 2015-2017. Fruit oil content as well as some of physiological traits and antioxidant activities under control and drought stress conditions were evaluated. The results of combined analysis of variance (ANOVA) for fruit yield and other measured traits showed that year, irrigation treatments, genotype main effects and their interactions were highly significant. In general, fruit yield, relative water content (RWC), oil content and total soluble proteins (TPs) showed a decreasing trend, whereas the electrolyte leakage, H2O2 content and activity of catalase (CAT), ascorbate peroxidase (APX) and peroxidase (POX) displayed an increasing trend in the tested olive genotypes during drought stress. A Principal component analysis (PCA)-based biplot demonstrated that stress tolerance index (STI) positively correlated with POX and TPs. Results also revealed a high level of genetic diversity in the tested olive genotypes, and among them, two commercial (Abou-satl) and promising genotypes (T2) responded better to drought by marinating a good balance for fruit yield and some of the antioxidant activities. These genotypes could be used in future programs to develop new olive cultivars with beneficial stress-adaptive traits.